Interactive eBook Applications in the Context of the Modern Media System: Release and Promotion Strategies - L. V. Zimina (Библиосфера, 2022)
The article treats digital technologies impact on modern ways of content producing, promotion and consumption. The focus is on interactive book apps as innovative publishing projects that use interactive multimedia content. Interactive book apps are designed for tablets and smartphones and combine different elements (texts, images, video, audio, animation and so on). The author traces back in short e-books prehistory from Kindle gadgets to the time of innovative iPad tablet that resulted in a new generation of e-books. Different types of interactive book apps are highlighted in the article on the base of their purposes and genres (for examp.: fiction, non-fiction, for kids and so on); some of these apps have elements of critical edition. From theoretical point of view interactive book apps can be treated within the frame of the media convergence approach that tends to blur boundaries between contents of different types. Exactly from these stem theoretical and practical difficulties as follows: in the first case – with notions that could be applied to them, in the second one – with tools for their search, identification, systematization and preservation in archives. The article analyzes a number of limitations (technological, software, legal, socio-cultural) that hinder their dynamic development in the modern media system. Main strategies of apps’ output and promotion are generalized and a number of restrictions that hinders their actual development in the media system is analyzed.